A Prospective Clinical Observational Study on Protocol Based Sushrutas Avasthanusar Management of Pakshagata (Ischemic Stroke) (International Journal of Ayurveda and Pharma Research, 2021)
Stroke is one of the leading cause of death and the treatment so far has no promising results. Though ample research is being carried out for alleviating the disease and new avenues are being explored in acute management followed by physical rehabilitation and physiotherapy etc, yet the disease have not been dominated and remain incurable.. Pakshaghata treatment schedule adopted according to the stage i.e. in acute stage the immediate aim is to maintain the lifestyle and to prevent the further complications treatment based on avastha helps in reversal of pathology, so here protocol is developed which is already being followed giving promising results in acute conditions need to be documented.Objective: The study was undertaken to assess the efficacy of Avasthanusar chikitsa in the management of Ischemic stroke (Pakshagata).Methods:10 patients of acute ischemic stroke directly coming to Sushrut Ayurved Hospital were enrolled after confirming the CT/MRI as per diagnostic criteria and those who were fitting in inclusion criteria.All the 10 patients underwent  the who whole treatment protocol according to avastha but the time, medicines were totally individualised.Results:1.In Pitta samasargaja avastha Glass gow coma scale showed 91.49 % improvement which was highly significant.• In Kapha samasrgaj avastha NINDH stroke scale and Barthel index showed significant improvement of 83.7%.3 .In Vataja samsargaja avastha  Modified Rankin scale and 10 meter walk test showed 72.5%  & 86.21% improvement respectively which was highly significant.Interpretation And Conclusion:In Pittasamsargaja avastha when presenting symptoms are mada , murcha and akashepaka the both Dosha and vyadhi viparita chikitsa is done simultaneously by teekshana nasya and sheeta upakramas., Once pittaja laxanas are reduced kapaha/ amahara chikitsa is done, In vata samsargaja chikitsa Brihmana chikitsa is done.